ANALISIS PERBANDINGAN AKURASI MODEL PREDIKSI KEBANGRUTAN ANTARA MODEL ALTMAN DAN SPRINGATE PADA PERUSAHAAN SEKTOR PARIWISATA, RESTORAN, DAN HOTEL DI BEI - Dewi Harahap, Syanti; Saputra, Dasriyan; Husein Anhar, Ryn (Jurnal GeoEkonomi, 2025)
This study aims to analyze and compare the Altman Z''-Score bankruptcy method and the Springate S-Score method. The formulation of the problems in this study are: first, is there a significant difference in predicting bankruptcy using the Altman Z”-Score model and the Springate S-Score model, and secondly, is the most accurate bankruptcy prediction model in predicting the bankruptcy of tourism companies, restaurants and hotels in Indonesia Stock Exchange. The data used in this study are company financial reports published on the Indonesia Stock Exchange's website. The population used in this study are all tourism, restaurant and hotel sector companies on the Indonesia Stock Exchange. Data analysis techniques used non-parametric statistical tests, namely the Wilcoxon Signed Rank Test using SPSS, Accuracy and Error Testing using Microsoft Excel. The results of this study indicate that there is a significant difference between the Altman Z”-Score model and the Springate S-Score model in predicting bankruptcy, and the most accurate model in predicting bankruptcy is the Altman Z”-Score model with an accuracy rate of 72.72% of on the Springate S-Score model with an accuracy rate of only 63.63%.